Testing bounded rationality against full rationality in job changing behavior - Bruno Contini; Matteo Morini (Institute for the Study of Labor (IZA), 2007)
In this paper we question the hypothesis of full rationality in the context of job changing behaviour, via simple econometric explorations on microdata drawn from WHIP (Worker Histories Italian Panel). Workers' performance is compared at the end of a three-year time window that starts when choices are expressed, under the accepted notion that the main driving forces of job change are future real wages and expected job quality. Bounded rationality suggests that individuals will search for new options capable to attain satisfactory targets (aspirations levels, standards, norms), based on conditions prevailing in their own local environments. Our empirical strategy consists of appropriately defining such environments (cells) and observing the ex-post individual performance in relation to the degree of dispersion, clustering and mobility within and between cells. Under full rationality the following are to be expected: high inter-cell mobility, large dispersion around the targets, and clustering in the vicinity of the efficiency frontier. None of the above expectations are confirmed in this exploration. Our conclusion is that workers behave according to principles of rationality that seem distant from those of full rationality assumed in the vast majority of contemporary empirical (and theoretical) studies. The idea of bounded rationality à la Simon provides a better fit to our observations.
Keywords: 330; Bounded rationality; job changes; mobility; testing bounded rationality; Arbeitsmobilität; Beschränkte Rationalität; Rationales Verhalten; Italien